The Takeda Three Colors Combination Test: A Screening Test for Detection of Very Mild Alzheimer’s Disease - Shinya Takeda; Kayo Tajime; Toshiatsu Taniguchi (The Scientific World Journal)
Background. Alzheimer’s disease (AD) is the most common type of dementia and is prevalent worldwide. It is expected that AD, for which aging is a risk factor, will increase in the future. Because early detection of AD has become increasingly important, promoting demand for screening tests with adequate sensitivity. In this study, we examined the usefulness of the Takeda Three Colors Combination Test (TTCC) for screening of the very mild AD and amnestic mild cognitive impairment (aMCI). Methods. 154 senior persons participated in the research: 55 with very mild AD, 45 with aMCI, and 54 control group. The TTCC, which was a colored cards configuration memory task, was examined for sensitivity and specificity. Results. The sensitivity of the TTCC was 76% and 47% for the very mild AD and aMCI groups, and the specificity was 83%. Conducting TTCC (including instruction and evaluation) was accomplished within 2 minutes for all subjects. Conclusion. The TTCC is useful screening test for early detection of AD. Furthermore, administration time is short and requires no special training or skills. Thus, we believe the TTCC shows great potential for use as an AD screening test by a general practitioner in communities worldwide.